Poplex Manila a pop music complex for the promotion of music tourism - Mag-iba, Maria Andrea R.
Music tourism has made huge economic and cultural impacts in other countries. It involves individuals traveling to either listen to live performances or to experience history related to either the creation or performance of music. Music festivals are among the main attractions of the music tourism industry and they help promote not only the artists and their music but also support other industries like hospitality (food and accommodation) and transportation. Local music organizations have made recent efforts on how they could promote the music industry and one of these is by holding music festivals. This study aims to provide design solutions that will support the music tourism industry in the Philippines through studies of precedent structures and local music festivals, site visits and participatory observation. The study concludes with a design that, through its form, represents music concepts such as fluidity, structure, and repetition. For its function, specific venues were provided for the activities that were held during recent local music festivals, which, for the study, were assumed to still be held in succeeding events. Further studies on site circulation and additional facilities were among the major design recommendations.